Implementation of the decision tree method and C4.5 algorithm for teacher classification in obtaining web-based position promotion at SMK Al-Ihya Selajambe Kuningan - Sri Rama Putri (Jurnal Info Sains : Informatika dan Sains, 2024)
The quality of education is one of the factors of change and development in the field of education. The role of teachers is very important, because the performance development carried out will be an assessment, consideration and reference for obtaining promotions. SMK Al-Ihya Selajambe conducts teacher assessments once a year. So far, the assessment carried out in determining the classification of promotion is still carried out conventionally or not computerized so that it requires a lot of time and the assessment is not necessarily accurate, and there is no method in the teacher assessment process. Therefore, it is necessary to have a computerized system and a method that can help the school. The method used is decision tree and C4.5 algorithm with testing using RapidMiner application. The final results of this study obtained training data with an Accuracy value of 90.00%, precision of 80.00% and recall of 100.00% which is classified as very good. As well as testing data with an Accuracy value of 60.00%, precision of 50.00% which is classified as quite good and recall of 100.00% which is classified as very good.